NHERF4 hijacks Mas-mediated PLC/AKT signaling to suppress the invasive potential of clear cell renal cell carcinoma cells. (28th October 2021) - Yang, Ying; Liang, Jihuan; Zhao, Chunjuan; Chen, Yibin; Gu, Siyu; Yang, Xiaomei; Liu, Hua; Qin, Qiong; Wang, Haibo; Yang, Zhuoli; Cao, Xuedi; Feng, Duiping; et al.
Abstract: The Mas receptor has been reported to promote migration and invasion of clear cell renal cell carcinoma (ccRCC) cells via Ang-(1–7)-dependent AKT signaling. However, the mechanism underlying the regulation of Mas function remains unknown. Here, eight PDZ domain-containing proteins were identified as Mas interactors using surface plasmon resonance (SPR) coupled to mass spectrometry (MS). NHERF4 was the only downregulated gene across multiple independent ccRCC datasets. GST pull-down and co-immunoprecipitation assays confirmed physical interaction between NHERF4 and Mas. Using NHERF4 overexpression and knockdown assays, we found that NHERF4 inhibited Mas-induced migration, invasion and in vivo metastasis of ccRCC cells. Mechanistically, NHERF4 suppressed Mas-stimulated AKT phosphorylation and the PLC/Ca 2+ response. We further demonstrated that NHERF4 compromised Mas-mediated migration and invasion of ccRCC cells via regulation of the PLC/AKT signaling axis. Analysis of the ccRCC dataset revealed that low levels of NHERF4 expression were correlated with higher TNM stage, and independently predicted poor prognosis of ccRCC patients. Overall, our study identified NHERF4 as a novel regulator of ccRCC invasiveness, and a prognostic biomarker, which may be beneficial for determining optimal therapeutic strategies for ccRCC patients. Highlights: PDZ protein NHERF4 interacts directly with Mas and is downregulated in ccRCC. NHERF4 inhibits Mas-mediated invasive potential of ccRCC cells in vitro and in vivo . NHERF4 suppresses Mas/PLC/AKT signaling axis in ccRCC cells. Low NHERF4 expression is correlated with higher TNM stage and independently predicts poor prognosis of ccRCC patients.